"Florvision Enterprise" / Siti Zubaidah Azizan...[et.al] - Azizan, Siti Zubaidah; Abdullah, Nurhani; Awang Kechik, Noratikah; Abdul Rahman, Nur Asiah; Othman, Nuratiqah; Sheikh Ab Rahim, Siti Norafatidyah (Faculty of Plantation and Agrotechnology, 2014)
The name of our business is Florvision Enterprise. Our business type that we generate is partnership which is the partner has limited liability restricted to the percentages of amount capital invested. The profit or loss will incurred by each partner depend on how much amount capital invested by the partners. The relation among business partner is dictated by the agreement. E-photo is a concept of technological based-graphic photograph that have potential to be positioned as one of the successful photograph business throughout the country with our creative innovation. E-photo providing a photo services business with addition of graphic design and colorful photo editing. Besides that, our E-photo machine has advance function which can snap passport photo using visual and audio instruction. E-photo provides high quality photograph with unique graphic design at value pricing that affordable for our target market. Our business provides efficient service in term of processing the photo in short period of time and based on the customer preferences. Our overview for this industry is complex and fast growing due to the advance of technology. Nowadays, the photography industry becomes more evolve with the addition of graphic design. There are many educational institutions located in Malacca such as private and government educational institutions. Besides, there are many of shopping complexes such as AEON, Tesco, Mahkota Parade and others. Our services are open to all people especially teenagers and family.